La tradizione manoscritta della vita s. Pauli primi eremitae e le più antiche edizioni stampate di questa opera Geronimiana - Degórski, Bazyli (Vox Patrum, 2018)
The article is meant to present – in the first part – the results of the author’s research on the Manuscript Tradition of the Vita S. Pauli monachi Thebaei of St. Jerome and, in particular, what was surveyed through the continuation of the analysis by John Frank Cherf O.S.B. In the second part of the article the most ancient printed editions of the Vita S. Pauli monachi Thebaei of St. Jerome are reviewed.